APPLICATION OF THE QUANTUM TEACHING LEARNING MODEL IN MATHEMATICS SUBJECTS FOR CLASS IV STUDENTS AT INPRES TAMALANREA V MAKASSAR - Anggie Dwi Annisa; Muh. Fihris Khalik; Rahmawati (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
This research aims tto : (1) Apply the Quantum Teaching Learning Model in Mathematics for Class IV Students at SD Inpres Tamalanrea 5 Makassar, (2) To determine the factors mthat ingluence the improvement in mathematics learning outcomes for class IV SD Inpres Tamalanrea 5 in Makassar City. The Quantum Teaching Learning model can imrove mathematics learning for fourth grade students at SD Inpres Tamalanrea 5, Makassar city. The increase in the value of learning outcomes can be seen both from student learning activities which increase from cycle II, as well as from test results, which are obtained at the end of each cycle during the learning process.